Journalistic Photography Training To Enhance Children's Visual Literacy Through The Collaboration of Cia, Warior and Imde - Safrudiningsih; Nurohmat; Suradi; Sisca T Gurning; Erwin Mulyadi (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The rapid advancement of digital technology has brought children into closer contact with various forms of visual information, particularly photographs and videos disseminated through social media platforms. However, the ease of capturing and distributing images is not always accompanied by adequate skills in understanding visual messages, identifying news values, and applying ethical principles in the use of photographs. This community service activity aims to introduce the fundamentals of photojournalism to children through a strategic collaboration between CIA Magazine, Warior (Junior Journalists), and the Institut Media Digital Emtek (IMDE). The activity is scheduled for July 30, 2026, involving 9 children as participants. The implementation method employs a participatory approach and practice-based learning, consisting of an introduction to photojournalism, instruction on photographic composition, introduction to the 5W+1H elements, hands-on photography practice, caption writing, participant work presentations, and evaluation. Through this activity, participants are guided to produce photographs that are not only visually appealing but also informative, story-driven, and journalistically valuable. This initiative is expected to strengthen children's visual literacy, creativity, environmental sensitivity, communication confidence, and understanding of ethics in photographing and publishing images.